Dispersal limitation, eutrophication and propagule pressure constrain the conservation value of Grassland Green Infrastructure. (June 2021) - Hooftman, Danny; Kimberley, Adam; Cousins, Sara A.O.; Escribano-Avila, Gema; Honnay, Olivier; Krickl, Patricia; Plue, Jan; Poschlod, Peter; Traveset, Anna; Bullock, James M.
Abstract: Semi-natural grasslands harbour many of Europe's species of conservation interest. Although larger grasslands are the focus of most conservation activity, many grassland fragments are scattered across landscapes –in small patches or along linear elements– which can form Grassland Green Infrastructure (GGI). GGI has the potential to enhance landscape diversity by creating functioning metacommunities comprising of large semi-natural grasslands and these surrounding fragments. While often highlighted in conservation policy, little is known about the biodiversity supported by green infrastructure itself and thus its conservation potential. To address this issue, we contrasted plant communities in 36 'core' grassland sites across three European countries with communities in the surrounding GGI. We related compositional differences to amount and type of GGI habitat (patches or linear), and the distances for seed dispersal by livestock from core sites. We found substantial differences between the GGI and the core sites, with a mean 54% species turn-over. These differences indicated filtering of stress tolerant species characteristic of low nutrient conditions, and semi-natural grassland specialists. Species with poorer dispersal abilities declined strongly with increasing distances from the core sites. The many additional species in the GGI, not found in the core sites, were predominantly those with a competitive strategy and high seed dispersal ability. We conclude that the biodiversity-supporting role of GGI across Europe is severely constrained by eutrophication, dispersal limitation and external propagule pressure. Actions to improve the quality of GGI might include enhancing dispersal by livestock combined with more type-diversification and less intensively used grassland habitats. Highlights: Conservationists promote Green Infrastructure (GI) to support habitat connectivity. But the actual conservation value of GI is rarely assessed empirically. We find GI has limited conservation value for grasslands across three countries. GI value is constrained by eutrophication, dispersal limitation and seed pressure. Enhancing dispersal and diversifying component habitats could increase GI value.